Core conversion design study of TRIGA Mark 2000 Bandung using MTR plate type fuel element. (2018) - Pinem, Surian; Sembiring, Tagor Malem; Surbakti, Tukiran
The TRIGA 2000 Bandung (TRIGA 2000) is a TRIGA Mark II type reactor with the nominal thermal power of 2 MW. It is used as a back-up reactor for irradiation radioisotope targets to the local market. This present study describes the fuel type conversion, from TRIGA fuel rod type to the MTR fuel plate type, as a solution to the fuel shortage. The optimum silicide (U3 Si2 -Al) equilibrium core are obtained by using WIMSD/5B (cell calculations) and BATAN-FUEL and BATAN-3DIFF (core calculations) codes for static and kinetic core parameters. The core calculation results showed that the optimum equilibrium core configuration is 5×5 core grid position and the maximum thermal neutron fluxes in the centre and periphery core are 6.07×10 13 neutron/cm 2 s and 1.41×10 13 neutron/cm 2 s, respectively. It is concluded that TRIGA 2000 reactor can be designed with very satisfactory static parameters and inherent safety.